التنفيذ التعاضدي لبروتوكول ناغويا والمعاهدة الدولية بشأن الموارد الوراثية النباتية للأغذية والزراعة: سيناريوهات ينبغي أخذها بالاعتبار من قبل نقاط الاتصال الوطنية وأصحاب المصلحة المهتمين الآخرين - Joint Capacity Building Programme (2019)
Bioversity International works with a wide range of international and national partners to implement the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) and the Nagoya Protocol of the Convention on Biological Diversity in mutually supportive ways.